Association of Red Blood Cell Distribution Width-Albumin Ratio for Acute Myocardial Infarction Patients with Mortality: A Retrospective Cohort Study - Li, Dan; Ruan, Zhishen; Wu, Bo (Clinical and applied thrombosis/hemostasis, 2022)
Background Red blood cell distribution width (RDW) was a risk factor for poor prognosis in acute myocardial infarction (AMI). Recent reports suggested that combining RDW with other laboratory metrics could provide a better prediction. This retrospective study aimed to investigate whether the RDW-albumin ratio (RAR) may be associated with mortality after an AMI. Methods This cohort study was conducted among adults (over 16 years old) with AMI in the Medical Information Mart for Intensive Care Database III V1.4 (MIMIC-III). The primary outcome was 30-day mortality, and the secondary outcome was 1-year and 3-year mortality. Cox hazard regression model and Kaplan–Meier survival curves were constructed to estimate the effect of biomarkers on mortality. We used three models to adjust for potential bias. Receiver operating characteristic (ROC) curves and the area under the curve (AUC) were analyzed for the excellent performance of RAR on prognosis. Results A total of 826 patients were eventually enrolled in our study. In multivariate analysis, RAR was found to be associated with 30-day mortality (Model 3: HR = 1.23, 95% CI = 1.09-1.39, P < .001). In addition, Subgroup analysis showed that the effect of RAR was higher in female patients than in male patients (P for interaction = .026). Kaplan-Meier survival curves showed that patients in the lower RAR quartile tended to have higher survival rates in the short and long term. AMI patients with RAR ≥ 4 had a 122% increase in 3-year mortality. Results of ROC and AUC showed that the prognostic performance of RAR for mortality was the best (30-day mortality: 0.703; 1-year mortality: 0.729; 3-year mortality: 0.737). Conclusions RAR is a simple and stable predictor of prognosis in AMI patients. Our results support RAR = 4.0 as a criterion for prognostic risk stratification of AMI patients.